Effects of the Center Units of Small‐Molecule Donors on the Morphology, Photovoltaic Performance, and Device Stability of All‐Small‐Molecule Organic Solar Cells. Issue 10 (2nd September 2021) - Li, Shaman; Ma, Qing; Qiu, Beibei; Meng, Lei; Zhang, Jinyuan; Wu, Yilei; Zhang, Zhanjun; Zhang, Zhi-Guo; Li, Yongfang
Abstract : Rational design and synthesis of new small‐molecule donors are critically important to achieve highly efficient small‐molecule organic solar cells (SM‐OSCs) with desirable device stability. Herein, two new acceptor–donor–acceptor (A–D–A) structured small‐molecule donor materials SM‐DTBDT and SM‐BDT with dithieno[2, 3‐d:2′, 3′‐d′]benzo[1, 2‐b:4, 5‐b′]dithiophene (DTBDT) and benzodithiophene (BDT) as the core D‐units are designed and synthesized, respectively. After thermal annealing treatment, the power conversion efficiencies (PCEs) of the SM‐DTBDT‐ and SM‐BDT‐based devices with Y8 as acceptor material reach 12.45% and 10.68%, respectively. The main reason for the different device performance can be ascribed to the different crystallinity and morphology features of the small‐molecule donor:Y8 blend films. Compared with the SM‐BDT:Y8 blend films, the SM‐DTBDT:Y8 blend films show a smoother surface, more uniform phase separation, mixed edge‐on and face‐on orientations, and enhanced crystallinity, resulting in the more efficient exciton dissociation and charge transport. In addition, it is observed that the SM‐DTBDT‐based devices also exhibit better stability. This work shows that fine‐tuning the center units of small‐molecule donors can not only increase the photovoltaic performance but can also be an effective method to improve the device stability. Abstract : Two new acceptor–donor–acceptor (A–D–A)‐type small molecule donors SM‐DTBDT and SM‐BDT with dithieno[2, 3‐d:2′, 3′‐d′]benzo[1, 2‐b:4, 5‐b′]dithiophene (DTBDT) and benzodithiophene (BDT) as the core D‐units, respectively, are synthesized and their photovoltaic performance results indicate that tuning the center units of the donors can increase the efficiency and improve the stability of the all small‐molecule organic solar cells.